Thermal management in electrical vehicle batteries using evolutionary algorithms - Shaurya, Baid (Nanyang Technological University, 2024)
The escalating concerns over greenhouse gas emissions have catalysed the development and widespread adoption of electric vehicles (EVs) and smart grid systems. This transition is buoyed by global environmental regulations, growing consumer climate consciousness, and the expansion of EV charging infrastructures. Lithium-ion batteries are central to this evolution due to their high energy density and effective charge cycles. However, the thermal management of these high-energy-density systems emerges as a critical challenge, with the imperative to ensure thermal safety and optimise performance being paramount for the longevity and reliability of EV batteries.